Ответы и объяснения

Лучший Ответ!
  • yliaks
  • светило науки
2014-03-07T16:49:07+00:00
1. (х + 3,8) - 5,4 = 72,85
    х + 3,8 = 72,85 + 5,4
     х + 3,8 = 78,25
     х = 78,25 - 3,8
     х = 74,45

2) (х - 23,58) + 37,6 = 150,78
    х - 23,58 = 150,78 - 37,6
    х - 23,58 = 113,18
    х = 113,18 + 23,58
     х = 136,76

3) 10,36 + (х - 56,051) = 120,309
     х - 56,051 = 120,309 - 10,36
     х - 56,051 = 109,949
     х = 109,949 + 56,051
     х = 166

4) 35,56 - (х + 12,07) = 18,49
    х + 12,07 = 35,56 - 18,49
    х + 12,07 = 17,07
    х = 17,07 - 12,07
    х = 5
спасибо тебе огромное))
всегда пожалуйста)